Manejo de plantas daninhas e sua influência sobre a biota do solo em cafeeiros no cerrado mineiro - Rodrigues, Rafael Jorge Almeida (2021)
Through a phytosociological survey, the objective was to evaluate the weed Community in coffee trees from the Denomination of Origin of the Cerrado Mineiro, in the rainy and dry seasons. The influence of the most used weed control methods in coffee growing was also investigated, on microbiological indicators such as biomass carbon (CBM), basal respiration (Resp.), Metabolic conscious (qCO2), arylsulfatase enzymes (Aryl.), Β- glucosidase (β-glu), acid phosphatase (Phosph.), FDA and urease, soil chemical parameters, macrofauna components such as carabidae and myrmecofauna. In the phytosociological survey, 26 coffee properties in 12 municipalities were visited. To carry out the survey, the square inventory method with an area of 1m2 was used. During the rainy season, 54 species were found, being Eleusine indica (goosegrass), the species with the highest number of individuals and importance value. In the dry period, 56 species were found, being the horseweed (Conyza sp.) with the highest number of individuals and importance value. For soil microbiological and chemical evaluation, and pitfall traps for the scarab and myrmecofauna soil, experiments were carried out in two coffee properties, called MK and MM. Weed control methods, mechanical mowing (RMEC), pre-emergence (HPRE) and post-emergence herbicide (HPOS), Congo signalgrass cultivation (CBRA) were evaluated in between rows (ELP) and rows (LIP) for coffee planting. For soil microbiological and chemical parameters, soil samples were collected in the rainy and dry seasons, between the rows (ELP) and planting rows (LIP) of the coffee trees. In the MK area, the highest values of the attributes CBM and Resp., Fosf, Urease and arylsulfatase in the CBRA, RMEC and SCAP methods in the rainy season. In the dry period, there was a substantial increase in CBM values in all methods in both locations and a reduction in Resp., qCO2, Urease and β-glu., values, especially in the RMEC and SCAP methods. In MM, in ELP, higher values of CBM in the first season was observed in HPRE, however, in the second season, except for SCAP, the values of this attribute decreased. In LIP, the values were lower for the activities of the enzymes Aril., Fosf. and urease. In the chemical attributes of the soil, the HPRE method showed the lowest potassium content (K) in ELP and CBRA in LIP in MK, with no differences in MM For myrmecofauna, it was found that the ant species in higher numbers were: Pheidole sp.2, Pheidole sp.1, Brachymyrmex sp.1, Dorymyrmex sp.1, Megalomyrmex sp.1 and Pheidole sp.5. In MK, the CBRA method showed the highest number and exclusive species, in MM, the HPOS method showed the highest specie number. For the analysis of carabids, the most abundant species were Notiobia sp.1, Selenophorus sp.1 and Trichopselaphus sp.1. The methods that presented the highest species richness and abundance of individuals in descending order were RMEC (8 and 40), SCAP (7 and 33), HPRE (5 and 27), CBRA (3 and 27) and HPOS (4 and 24). Weed control methods, mainly SCAP, CBRA and RMEC favored changes in soil microbiological, chemical and macrofauna attributes.